Biological production of H2, CH4 and CO2 in the deep subsurface of the Iberian Pyrite Belt. (8th June 2021) - Sanz, Jose L.; Rodriguez, Nuria; Escudero, Cristina; Carrizo, Daniel; Amils, Ricardo
Summary: Most of the terrestrial deep subsurfaces are oligotrophic environments in which some gases, mainly H2, CH4 and CO2, play an important role as energy and/or carbon sources. In this work, we assessed their biotic and abiotic origin in samples from subsurface hard‐rock cores of the Iberian Pyrite Belt (IPB) at three different depths (414, 497 and 520 m). One set of samples was sterilized (abiotic control) and all samples were incubated under anaerobic conditions. Our results showed that H2, CH4 and CO2 remained low and constant in the sterilized controls while their levels were 4, 4.1 and 2.5 times higher respectively, in the unsterilized samples compared to the abiotic controls. The δ 13 CCH4 ‐values measured in the samples (range −31.2 to −43.0 ‰) reveals carbon isotopic signatures that are within the range for biological methane production. Possible microorganisms responsible for the biotic production of the gases were assessed by CARD‐FISH. The analysis of sequenced genomes of detected microorganisms within the subsurface of the IPB allowed to identify possible metabolic activities involved in H2 ( Rhodoplanes, Shewanella and Desulfosporosinus ), CH4 (Methanobacteriales) and CO2 production. The obtained results suggest that part of the H2, CH4 and CO2 detected in the deep subsurface has a biological origin.